STRENGTHENING THE POTENTIAL AND PROMOTION OF WRINGINANOM TOURISM VILLAGE THROUGH DIGITAL BRANDING - Kusumawati, Yudhistya Ayu; Kukuh Lukiyanto; Elizabeth Paskahlia Gunawan; Jeremiah Calvin; Lita Rachel Hoo (SEEIJ (Social Economics and Ecology International Journal), 2026)
Tourism is an important aspect as part of the government's main focus. Based on the situation analysis, Malang Regency has the Bromo Tengger Semeru National Park Area (TNBTS) which is the top seven national tourist destinations. Wringinanom Tourism Village (DEWI ANOM) is in Malang Regency, East Java, and is the entrance to the Bromo Tengger Semeru tourist route via Malang which has several tourism potentials including education, culture and adventure. Apart from offering natural beauty and economic potential in the form of agricultural horticultural products, Wringinanom Village offers educational, cultural and adventure tourism for tourists. However, this tourist village area still needs to be developed optimally by the Village Government, including strengthening the potential and promoting tourist villages. In this case, Human Resource awareness plays a very important role in tourism promotion activities. So, the main problem raised in this community service activity is related to the marketing aspect. Community service with the Binus Bangun Desa scheme aims to increase HR capacity in Destination Management and Optimizing Digital-based Tourism Product Marketing in the tourism awareness group, Wringinanom Village. The activities that will be carried out in this community service program will implement digital branding including visual indentity as an effort to digitize and optimize the Wringinanom